Peran Pendidikan Islam dalam Membentuk Karakter di Tengah Transformasi Teknologi 4.0 dan Society 5.0 - syahrainy, alfi; Rahmi, Elvi; Nufus, Faizatun; Puspika Sari, Herlini (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The Digital Era 4.0 and 5.0 have caused various new challenges and opportunities in the world of education, especially in Islamic education which has an important role in shaping students' character. This study aims to investigate the contribution of Islamic education to the formation of students' character in the digital era and identify the various challenges that arise. The method used is a literature study with an analysis of relevant literature. The results of the study show that Islamic education not only instills moral and ethical values, but also acts as a tool for unverified information. Although there are challenges such as inequality in access to technology and the possibility of spreading misinformation, Islamic education is able to utilize digital technology to improve the quality of the learning process.